Effects of probiotic treatment on patients and animals with chronic obstructive pulmonary disease: a systematic review and meta-analysis of randomized control trials - Su, Ziying; Ma, Chenxi; Ru, Xiaosong; Zhang, Sijia; Wu, Chuyi; Huang, Yue; Cen, Huijie; Yin, Zihui; Zhang, Jianping (Frontiers in Cellular and Infection Microbiology, 2024)
ObjectiveIn recent years, the lung-gut axis has received increasing attention. The oxidative stress and systemic hypoxia occurring in chronic obstructive pulmonary disease (COPD) are related to gut dysfunction. That suggests probiotics have a potential therapeutic role in COPD. In this study, we therefore evaluated the ameliorative effects of probiotics on COPD.MethodsSearches were conducted in four electronic databases, including PubMed, Cochrane Library, the NIH clinical registry Clinical Trials. Gov and EMBASE. The data extracted was analyzed statistically in this study using StataMP17 software, with mean difference (MD) chosen as the effect size for continuous variables, and the results expressed as effect sizes and their 95% confidence intervals (CIs). Standardized Mean Difference (SMD) was used if the data units were different.ResultsWe included three randomized, controlled, double-blind clinical trials and five randomized controlled animal studies. The results show that for lung function, probiotics improved %FEV1 in COPD patients (MD = 3.02, 95%CI: 1.10, 4.93). Additionally, in inflammation, probiotics increased IL-10 (SMD = 1.99, 95%CI: 1.02, 2.96) and decreased inflammatory markers such as TNF-α (SMD= -2.64, 95%Cl: -3.38, -1.90), IL-1β (SMD= -3.49, 95%Cl: -4.58, -2.40), and IL-6 (SMD= -6.54, 95%Cl: -8.36, -4.73) in COPD animals, while having no significant effect on C-reactive protein (MD = 0.30, 95%CI: -0.71, 1.32) in COPD patients. For lung structure, probiotics significantly reduced the degree of pulmonary collagen fibers deposition in COPD animals (SMD = -2.25, 95%CI: -3.08, -1.41).ConclusionOverall, probiotics may be an additional approach that can improve COPD. Further clinical trials are needed to evaluate the efficacy, safety, and impact factors of probiotics for COPD.Systematic Review Registrationhttps://inplasy.com/inplasy-2023-4-0023/, identifier INPLASY202340023.